2021
DOI: 10.1038/s41467-021-26489-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatic driver mutation prevalence in 1844 prostate cancers identifies ZNRF3 loss as a predictor of metastatic relapse

Abstract: Driver gene mutations that are more prevalent in metastatic, castration-resistant prostate cancer (mCRPC) than localized disease represent candidate prognostic biomarkers. We analyze 1,844 localized (1,289) or mCRPC (555) tumors and quantify the prevalence of 113 somatic driver single nucleotide variants (SNVs), copy number aberrations (CNAs), and structural variants (SVs) in each state. One-third are significantly more prevalent in mCRPC than expected while a quarter are less prevalent. Mutations in AR and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…We confirmed the prognostic and risk stratification utility of previously studied gene level CNAs and other alterations [2,[9][10][11][12]. For example, the CNAs of oncogenes and tumour suppressor genes, such as PIK3CA, CHD1, MYC, PTEN, CCND1, CDKN1B, TP53, CCNE1, NKX3.1, and RB1, have previously been shown to impact prognosis, tumour progression, and disease stage of PCa and other cancers [2,[17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Furthermore, molecular alterations of androgen receptor pathway genes, including AR, MED12, FOXA1, NCOR1, NCOR2, SPOP, NCOA2, and ZBTB16, have similarly been associated with different disease stages [2,22,33,37,38,[48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We confirmed the prognostic and risk stratification utility of previously studied gene level CNAs and other alterations [2,[9][10][11][12]. For example, the CNAs of oncogenes and tumour suppressor genes, such as PIK3CA, CHD1, MYC, PTEN, CCND1, CDKN1B, TP53, CCNE1, NKX3.1, and RB1, have previously been shown to impact prognosis, tumour progression, and disease stage of PCa and other cancers [2,[17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Furthermore, molecular alterations of androgen receptor pathway genes, including AR, MED12, FOXA1, NCOR1, NCOR2, SPOP, NCOA2, and ZBTB16, have similarly been associated with different disease stages [2,22,33,37,38,[48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, molecular alterations of androgen receptor pathway genes, including AR, MED12, FOXA1, NCOR1, NCOR2, SPOP, NCOA2, and ZBTB16, have similarly been associated with different disease stages [2,22,33,37,38,[48][49][50][51][52]. Besides AR, NCOA2, and ZBTB16, whose copy number changes were previously associated with late-stage diseases, the molecular alterations found in other members of the pathway were mainly somatic point mutations and altered expressions [2,18,30,34,35,[45][46][47][48]. However, this study found that MED12, FOXA1, NCOR1, NCOR2, and SPOP exhibited copy number changes that were associated with disease stages.…”
Section: Discussionmentioning
confidence: 93%
“…Blood is commonly used in diagnostics but low in cfDNA concentration while semen is, partly, secreted from the prostate and high in cfDNA concentrations [ 21 , 22 ]. Considering the variety of genetic alternations in PCa (113 mutations in 72 driver gene loci), we focused on epigenetic modifications which are restricted to promoters and retain specific patterns within the same cancer model [ 23–25 ]. DNA methylation microarray analysis containing 385,000 probes revealed 20 most significantly altered loci comparing PCa tissue and prostate tissue from BPH patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZNRF3 deep deletions are also observed in primary and metastatic prostate cancer (≤2%) ( Tables S1–S4 ), potentially promoting Wnt signaling via the stabilization of FZD receptors and Wnt co-receptors at the plasma membrane. Nevertheless, the frequency of ZNRF3 genomic loss was recently reported to be markedly higher (29.9% of metastatic and 9.54% of localized prostate cancers), and ZNRF3 loss positively correlates with biochemical recurrence and metastatic relapse of localized disease [ 140 ]. Future investigations exploring the role of clinically relevant genetic aberrations in RNF43 and ZNRF3 during primary and metastatic prostate cancer will be important to ascertain their impact on Wnt signaling.…”
Section: Activation Of the Wnt Pathway In Prostate Cancermentioning
confidence: 99%